Peran Kepala Sekolah Sebagai Pemberdayaan Sumber Daya Manusia Di SMA Berbasis Islam Bangkalan Madura - Hattahin, Hattahin; Widodo, Estu (Jurnal Kebijakan dan Pengembangan Pendidikan, 2019)
Abstract: The success of schools in improving the quality of education cannot be separated from the role of the principal. Headmaster. This study aims to describe (1) the role of the principal as empowering the human resources of the teaching and educational staff. (2) supporting factors for the success of school principals as empowering human resources for teaching and educational staff. (3) obstacles faced by school principals as empowering human resources for teaching and educational staff. (4) Headmasters' efforts as empowering human resources for teaching and educational staff in overcoming school problems. This research uses a multi-site study. This research was conducted at Senior High School YKHS and Senior High School Darul Munir. Data obtained through interviews, observation, and study documentation. The results of this study indicate that (1) the role of the head of YKHS and Darul Munir senior high schools as empowering human resources is to involve teachers and staff in managing school programs, managing curriculum, creating a conducive learning climate and achievement, involving teachers in training to improve their competence, facilitate facilities and infrastructure to support school activities, plan budgets, conduct student management activities, specifically assign teachers to oversee the program, and conduct supervision. (3) Internal factors that support success are the togetherness of the teachers to optimize their potential and the sincere desire to run the school program that has been planned together. External factors are strong student guardian support for programs that have been run by schools. (3) Internal constraints faced are limited time from teachers to carry out or run the program to the maximum extent possible. The external obstacle is the student's guardian awareness of the school program. (4) Efforts made in improving the quality of schools to overcome internal and external problems are communicating to teachers to be more active in carrying out or carrying out planned programs.Keywords: Principal, Empowerment, Human Resources.Â Abstrak: Keberhasilan sekolah dalam menigkatkan mutu pendidikan tidak lepas dari peran kepala sekolah. Kepala sekolah. Penelitian ini bertujuan untuk mendeskripsikan (1) peran kepala sekolah sebagai pemberdayaanan SDM tenaga pendidik dan kependidikan. (2) faktor pendukung keberhasilan kepala sekolah sebagai pemberdayaanan SDM tenaga pendidik dan kependidikan. (3) kendala yang dihadapi kepala sekolah sebagai perberdaya SDM tenaga pendidik dan kependidikan. (4) upaya Kepala Sekolah sebagai pemberdayaanan SDM tenaga pendidik dan kependidikan dalam mengatasi masalah sekolah. Penelitian ini menggunakan studi multisitus. Penelitian ini dilakukan di SMA YKHS dan SMA Darul Munir. Data diperoleh melalui wawancara, observasi, dan studi dokumentasi. Hasil penelitian ini menunjukan bahwa (1) peran kepala SMA YKHS dan SMA Darul Munir sebagai pemberdayaan SDM yaitu melibatkan guru dan pegawai dalam pengelolaan program sekolah, melakukan pengelolaan kurikulum, mewujudkan iklim belajar dan berprestasi yang kondusif, mengikutkan guru-guru dalam pelatihan untuk meningkatkan kompetensinya, memfasilitasi sarana dan prasarana pendukung kegiatan sekolah, merencanakan penganggaran, mlakukan kegiatan pengelolaan kesiswaan, menugaskan secara khusus guru-guru untuk mengawal program, dan melakukan pengawasan. (3) Faktor internal yang menjadi pendukung keberhasilan yaitu kebersamaan guru-guru untuk mengoptimalkan potensi yang dimiliki dan keinginnan yang ikhlas untuk mejalankan program sekolah yang telah direncankan bersama-sama. Faktor eksternalnya yaitu dukungan wali murid yang kuat pada program yang telah dijalankan oleh sekolah. (3) Kendala internal yang dihadapi adalah keterbatasan waktu dari guru-guru untuk melakukan atau menjalankan program dengan semaksimal mungkin. Kendala eksternalnya adalah kesadaran wali murid akan program sekolah tersebut. (4) Upaya yang dilakukan dalam meningkatkan mutu sekolah untuk mengatasi masalah internal dan eksternal adalah mengkomunikasikan kepada guru-guru untuk lebih aktif melakukan atau menjalankan program yang telah direncanakan.Kata kunci: Kepala Sekolah, Pemberdayaanan, Sumberdaya Manusia